Respiratory muscle training induces additional stress and training load in well-trained triathletes—randomized controlled trial - Kowalski, Tomasz; Kasiak, Przemysław Seweryn; Rebis, Kinga; Klusiewicz, Andrzej; Granda, Dominika; Wiecha, Szczepan (Frontiers in Physiology, 2023)
Background: Respiratory muscle training (RMT) has been investigated in the context of improved athletic performance and pulmonary function. However, psychophysiological costs of RMT remain understudied. Voluntary isocapnic hyperpnoea (VIH) and inspiratory pressure threshold loading (IPTL) are widely applied RMT methods. The main purposes of this study were to assess whether RMT induces additional load on well-trained triathletes and determine differences in RMT-induced load between sexes and applied methods. Materials and Methods: 16 well-trained triathletes (n = 16, 56% males) underwent 6 weeks of VIH or IPTL program with progressive overload. Blood markers, subjective measures, cardiac indices, near-infrared spectroscopy indices, inspiratory muscle fatigue, and RMT-induced training load were monitored pre-, in and post-sessions. We used multiple ANOVA to investigate effects of sex, training method, and time on measured parameters. Results: There were significant interactions for acid-base balance (p = 0.04 for sex, p < 0.001 for method), partial carbon dioxide pressure (p = 0.03 for sex, p < 0.001 for method), bicarbonate (p = 0.01 for method), lactate (p < 0.001 for method), RMT-induced training load (p = 0.001 for method for single session, p = 0.03 for method per week), average heart rate (p = 0.03 for sex), maximum heart rate (p = 0.02 for sex), intercostales muscle oxygenation (p = 0.007 for testing week), and intercostales muscle oxygenation recovery (p = 0.003 for testing week and p = 0.007 for method). Conclusion: We found that RMT induced additional load in well-trained triathletes. Elicited changes in monitored variables depend on sex and training method. VIH significantly increased subjective training load measures. IPTL was associated with disbalance in blood gasometry, increase in lactate, and reports of headaches and dizziness. Both methods should be applied with consideration in high-performance settings.